ASSOCIATION OF B-CELL LYMPHOMA PROTEIN-2 AND CASPASE-3 EXPRESSION IN OVARIAN CANCER - Budiana, I N. G. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2013)
Ovarian cancer remains a major problem of women’s health in the world, including Indonesia, and is associated with high rates of incidence and mortality. There are many efforts in early diagnosis on ovarian cancer, but until now there have not been found any satisfactory method. On the other hand, knowledge and research in the field of molecular biology become more advance, one of them is a mechanism to control the growth of cells in ovarian cancer through a process of programmed cell death or apoptosis. B-cell lymphoma protein 2 (Bcl-2) and caspase-3 are proteins that play a role on the mechanism of apoptosis. The purpose of this study was to determine the expression of Bcl-2 and caspase-3 and their association with ovarian cancer. Materials and method: The design of this study was a cross-sectional study. Expression of Bcl-2 and caspase-3 examined by immunohistochemistry under light microscope with 400x light power field and expression as a negative when the protein expressed in 10% or less of cells and as a positive when the protein expressed in more than 10% of cells. A number of 45 subjects were recruited in this study. Thirthy one of 45 subjects showed the expression of Bcl-2 positive (68.9%), while the positive expression of caspase-3 present in 20 subjects (44.4%). There was a significant association between the expression of Bcl-2 with the expression of caspase-3 in ovarian cancer patients ( p =0.002; lambda=0.4). There was also a significant association between stage of disease with expression of Bcl-2 ( p =0.002; lambda=0.3) dan expression of caspase-3 ( p =0.001; lambda=0.3). Conclusion: It concluded that there is a significant association between the expression of Bcl-2 and the expression of caspase-3 in ovarian cancer.
Keywords: Ovarian, cancer, Bcl-2 expression, Caspase-3 expression